Effect of CH4/SiCl4 ratio on the composition and microstructure of 〈110〉-oriented β-SiC bulks by halide CVD. Issue 4 (April 2017) - Tu, Rong; Zheng, Dingheng; Cheng, Hong; Hu, Mingwei; Zhang, Song; Han, Mingxu; Goto, Takashi; Zhang, Lianmeng
Abstract: Halide chemical vapor deposition process was carried out for fast fabricating oriented stoichiometric β-SiC through controlling flow rate of precursors (SiCl4 and CH4 ). The effects of molar ratio of C and Si precursors ( R C/Si ) on composition, preferred orientation, microstructure and deposition rate ( R dep ) were investigated. The deposits transformed from silicon-rich to stoichiometric β-SiC to carbon-rich with increasing R C/Si . 〈110〉-oriented stoichiometric β-SiC with lower density of defects were obtained at R C/Si in the range of 0.86–1.00, where the maximum R dep was 883 μm/h at R C/Si  = 1.00, leading to a thickness of 1.7 mm in 2 h deposition. Formation of ridge-like morphology has been discussed based on a twin plane propagation model.